Consumer.ology : the market research myth, the truth about consumers and the psychology of shopping - Graves, Philip (Nicholas Brealey, 2010)
"Explains the folly of using market research to make corporate decisions, describing examples of expensive mistakes made by corporations from General Motors to Mattel, and offers organizations an approach to better understand their customers."